On Vocabulary Learning Strategies of Chinese Non-English Majors - Zhang, Zhiqiang; Lu, Jie (International Journal of English Literature and Social Sciences (IJELS), 2019)
The paper attempts to investigate the overall pattern of English vocabulary learning beliefs and strategies used by some Chinese non-English major students, and further investigate the correlation between students’vocabulary learning beliefs, vocabulary learning strategies, and the scores on a vocabulary size (VS) test and an in-depth vocabulary knowledge (DVK) test. Three instruments are used to gather data for this study: Nation’s Vocabulary Levels Test (1990), Read’s Word Association Format (1998), and a questionnaire on VLSadapted from Gu and Johnson’s (1996). The questionnaires and the two tests are administered to college students majoring in science from the Shandong University of Technology. Descriptive statistics and correlation analysis are conducted to analyze the data collected. The results of this study show that: Firstly, most learners hold the belief that words should be learned in context and use while the belief that words should be memorized is not popular. Most students believe that learners should not only make efforts to enlarge their vocabulary size but also pay sufficient attention to various aspects of vocabulary knowledge. The learning beliefs do have an influence on their achievement in vocabulary learning. Secondly, students employ a wide range of VLS in their foreign language learning at meta-cognitive, cognitive and social/affective levels, but the frequency of overall VLS use is not high. In terms of the three categories of VLS, the most frequently used one is the cognitive strategy, and the least frequently used one is the social/effective strategy, with the meta-cognitive strategy in between. The students’ strategy use is generally the result of their previous learning experience, the influence of their teachers’ teaching methods, traditional Chinese culture, oriental students’ characters and the specific learning environment in China. Finally, the results indicate that most strategies are significantly correlated with the VS and DVK scores. At meta-cognitive level, plan to make & plan to implement strategies, learner autonomy strategies, and reviewing& testing strategies have a significant positive correlation with the two scores. Selective attention strategies have a significant positive correlation with the DVK scores. At the cognitive level, guessing strategies and note-taking strategies have a significant positive relationship with both the scores on VS and DVK tests. Dictionary use strategies have a significant positive correlation with the DVK scores.